HUBUNGAN PELAKSANAAN PROGRAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DENGAN KUALITAS SANITASI LINGKUNGAN DI LINGKUNGAN III KELURAHAN TANJUNG SELAMAT KECAMATAN MEDAN TUNTUNGAN TAHUN 2021 - Pitto Pratiwi Malau; Ripai Siregar; Muhraza Siddiq; Evfy Septriani Ginting; Ana Apriana (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2023)
Environment Sanitation is the health status of environment that focuses on monitoring various factors environment that is needed to provide a healthy environment that meets health requirements. Based on data obtained from Public Health Center of Medan Tuntungan related to community sanitation is still not good enough. Of the 236 households there are several of families who have not access latrines (20%), household waste processing (48.8%) and waste water disposal facilities that were still in Unprotected Sewerage category (70%). The purpose of this study was to determine the purpose of implementing a community based total sanitation quality in the region III Tanjung Selamat Medan Tuntungan 2021. The type of this research was observational analytic with cross sectional approach. The independent variables in this study include latrine access, household waste processing, waste water disposal and family drinking water treatment sources. With the acquisition of a sample of 70 families using simple random sampling technique and analyzed using Chi Square statistical test with a significance level of 95% (α=0.005). through the result of this study, it was found that there was a relationship between latrine access (p=0.023), household waste processing (p=0.006), waste water disposal (p=0.000) with environmental sanitation quality and there was no relationship between source and family drinking water treatment with environmental sanitation quality. Keywords : Environment Sanitation, Community Based Total Sanitation.